Editorial / Uvodnik - Krajnčan, Mitja (Revija za elementarno izobraževanje, 2021)
Also in the educational space, social pedagogy has been receiving an increasingly relevant position. In their contributions the authors display a wide array of activities of the rather young discipline, with orientation into work with children and adolescents with behavioural and emotional difficulties and disorders representing the dominant content. Confronted with an inflation of studies and publications of the quite small circle of research cadre, the papers represent an important scientific contribution.